2013
DOI: 10.1021/ac401555n
|View full text |Cite
|
Sign up to set email alerts
|

Nontargeted Profiling of Coenzyme A thioesters in biological samples by tandem mass spectrometry

Abstract: Coenzyme A (CoA) thioesters are ubiquitously present in metabolic networks and play a pivotal role in enzymatic formation and cleavage of carbon-carbon bonds. We present a method allowing nontargeted profiling of CoA-thioesters in biological samples. The reported UHPLC-MS/MS approach employes ion-pairing chromatography to separate CoA-metabolites carrying different chemical functionalities such as hydroxyl or multiple carboxyl groups and to distinguish between isomers. Selective detection of CoA-thioesters is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 32 publications
(57 reference statements)
0
47
0
Order By: Relevance
“…Moreover, it was shown that Stat3-mediated activation of the microRNA23a suppresses gluconeogenesis by targeting glucose-6-phosphatase expression [79]. Consistently, restoring gluconeogenesis by dexamethasone treatment showed significant inhibition of in vivo tumor growth [80]. A block in gluconeogenesis might contribute to the survival of HCC cells by increased usage of glycolysis and pentose phosphate pathway due to accumulation of glucose-6-phosphate [79].…”
Section: Metabolic Alterations In Liver Cancermentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, it was shown that Stat3-mediated activation of the microRNA23a suppresses gluconeogenesis by targeting glucose-6-phosphatase expression [79]. Consistently, restoring gluconeogenesis by dexamethasone treatment showed significant inhibition of in vivo tumor growth [80]. A block in gluconeogenesis might contribute to the survival of HCC cells by increased usage of glycolysis and pentose phosphate pathway due to accumulation of glucose-6-phosphate [79].…”
Section: Metabolic Alterations In Liver Cancermentioning
confidence: 84%
“…Ma et al showed in 2013 that this lack of gluconeogenesis might occur due to the decreased expression of 11β-hydroxysteroid dehydrogenase type 1 and an increased expression of 11β-hydroxysteroid dehydrogenase type 2. These enzymes control the activity of glucocorticoids [80]. Glucocorticoids promote gluconeogenesis, but in liver cancer cells the altered expression of 11β-hydroxysteroid dehydrogenase1/2 results in the insensitiveness of liver cancer cells to endogenous glucocorticoids [81].…”
Section: Metabolic Alterations In Liver Cancermentioning
confidence: 99%
“…Optima ammonium acetate, ammonium hydroxide, Optima LC-MS grade formic acid, acetonitrile, methanol, and water were purchased from Fisher Scientific, Agawam, MA. U- 13 Mice were fasted for 4 h before they were sacrificed by cervical dislocation and tissues were snap frozen in liquid nitrogen. Frozen tissues were stored at Ϫ80°C for further analysis (23).…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of 13 C Labeled Extract and Evaluation of Tissue Extraction Method-Escherichia coli strain NCM3722 (E. coli) was a generous gift from Joshua Rabinowitz's group (Princeton University). The E. coli culture and metabolite extraction method were modified from a previous studies (25,26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation